2010
DOI: 10.1007/jhep05(2010)085
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of J/ψ photoproduction at large momentum transfer at HERA

Abstract: The proton-dissociative diffractive photoproduction of J/ψ mesons has been studied in ep collisions with the ZEUS detector at HERA using an integrated luminosity of 112 pb −1 . The cross section is presented as a function of the photon-proton centre-ofmass energy and of the squared four-momentum transfer at the proton vertex. The results are compared to perturbative QCD calculations.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 52 publications
3
22
0
Order By: Relevance
“…Here K 1 is the modified Bessel function, and the dimensional parameter m ∼ Λ QCD will be constrained later. The replacement (9) introduces an exponential suppression at large distances, leaving the short-distance part unmodified. We will also consider the running coupling effects in our analysis.…”
Section: High Energy Evolution From the Jimwlk Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…Here K 1 is the modified Bessel function, and the dimensional parameter m ∼ Λ QCD will be constrained later. The replacement (9) introduces an exponential suppression at large distances, leaving the short-distance part unmodified. We will also consider the running coupling effects in our analysis.…”
Section: High Energy Evolution From the Jimwlk Equationmentioning
confidence: 99%
“…These measurements make it possible to constrain the total parton densities inside the proton to a very good precision. In addition, measurements of diffractive vector meson production [5][6][7][8][9][10][11][12][13] provide information on the spatial extent of the gluon distribution and in case of incoherent diffraction, even its fluctuations [14][15][16]. In the future, if an electron-ion collider is realized [17][18][19], DIS with a variety of nuclear targets will allow unprecedented detailed studies of proton and nuclear structure (see for example [20][21][22][23]).…”
Section: Introductionmentioning
confidence: 99%
“…[10] within framework of the QCD factorization theorem has demonstrated that the experimental data can be described if the energy dependence of two body pQCD scattering amplitude would be significantly slower at large −t, than at t = 0. Recently, a new experimental data on the photoproduction process γp → J/ψ + rapidity gap + X was reported [3]. This data also indicate a rather dramatic slowing down of the dependence of the cross section of this process on the energy with increase of −t.…”
Section: Introductionmentioning
confidence: 86%
“…(Such processes can be dubbed hard inelastic diffractive (HID) processes, in order to distinguish them from the diffractive processes, when the final particle remain a proton: X = p). These processes with V = J/ψ were extensively studied experimentally at HERA [1][2][3] due to a reasonably large cross section and a clean final state -production of an isolated charmonium state with large transverse momentum which is separated from the proton remnants by a large rapidity gap. Theoretically this process is advantageous, since the large charmonium mass m 2 V makes it possible to evaluate cross section of the process in perturbative QCD, for different values of transverse momentum transfer −t and virtuality of the photon Q 2 [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Hence also the BFKL Pomeron may carry non-zero transverse momentum, and the corresponding amplitude is governed by the non-forward BFKL Pomeron. This formalism was applied [5,6,[33][34][35] some time ago to the data from HERA on J/ψ, ρ and φ diffractive mesons photoproduction [1,2,36] with large transverse momentum p T and was shown to describe the data well. In this paper we revisit the diffractive J/ψ photoproduction at HERA and use the established description of this process to estimate the BFKL Pomeron loop contribution to inclusive vector meson hadroproduction.…”
Section: Contentsmentioning
confidence: 99%